Current and projected impacts of the parasite Tetracapsuloides bryosalmonae (causative to proliferative kidney disease) on Central European salmonid populations under predicted climate change. (20th April 2021) - Ros, Albert; Baer, Jan; Basen, Timo; Chucholl, Christoph; Schneider, Ernst; Teschner, Ruben; Brinker, Alexander
Abstract: Proliferative kidney disease (PKD) caused by the myxozoan parasite Tetracapsuloides bryosalmonae is an emerging salmonid disease implicated in recent declines in salmonid populations. Laboratory experiments have shown that the clinical symptoms of PKD exacerbate with increasing temperature. However, empirical evidence for a relationship between climate change and PKD driven declines in wild salmonid stocks is scarce. The current study uses both empirical data and ecological niche modelling to extrapolate future changes in temperature and precipitation on the spread of PKD in relation to changes in suitability of rivers for its primary bryozoan and secondary salmonid hosts. A 20‐year dataset on brown trout density using standardised method shows a decline of more than 50% in the population of the river Wutach, south‐western Germany at 536–755 m elevation. The decline coincides with higher prevalence of PKD. This decline was temperature related and driven by reduced local survival of parr to yearlings. Kidney hyperplasia was highest at low elevations and correlated negatively with trout density. Niche models based on state‐wide data show strong overlap in the areas suitable for T. bryosalmonae and its primary bryozoan hosts, and a strong link with temperature. Projections based on moderate to high emission‐case climate change scenarios predict a 50%–82% decrease in the area suitable for salmonids within this century, linked to PKD. The empirical data identify temperature‐mediated PKD as the underlying cause of the population decline. This relationship was corroborated by the niche modelling results. The highest losses are expected in projected salmonid suitable areas where salmonid habitats currently overlap with areas suitable for T. bryosalmonae . With ongoing climate change, both current and future populations are at severe risk to T. bryosalmonae and its associated disease PKD. Conservation efforts of salmonid stocks are dependent on climate mitigation and measures to help salmonids adapt to the disease.